A REPLY TO PETER LYTH ON WHETHER AN INFINITE TEMPORAL REGRESS OF EVENTS IS POSSIBLE. Issue 45 (5th January 2017) - Ter Ern Loke, Andrew
Abstract : Peter Lyth claimed that my argument against an infinite temporal regress of events conflates number as an abstract entity with number as a number of events or things. I show that my argument does not depend on such a conflation.